Geomorphological landforms in the Qais River basin (Tartous governorate) - سلوم, جولييت; المصطفى, تركية; صالح, نادين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study of geomorphological forms is the backbone for analyzing the characteristics of an area, in order to make the most of them before starting the various planning processes for that particular area. From this point of view, the current research focused on determining the nature of the geomorphological processes prevalent in the Qais River Basin area as well as showing the most important geomorphological units resulting from them. The present study made use of topographical and geological maps, field studies, in addition to the digital elevation model) ALOS PALSAR(. It became clear through the study that there is a diversity in the nature of the geographical distribution of the geomorphological units: some of which are structural, while others are kinetic-climatic. This finding provides the opportunity for a detailed study of these phenomena, which in turn, serve the diversity of developmental plans to achieve the optimal utilization of the land and the nature of its surface.